Does economic policy uncertainty affect insurance premiums? Fresh empirical evidence - Saeed Sazzad Jeris; Shahriar Frances; Mst Taskia Akter; Majed Alharthi (Heliyon, 2023)
Economic Policy Uncertainty (EPU) is the level of uncertainty or unpredictability arising from government policy on topics such as taxes, trade, monetary policy, and regulation. Exploring the relationship between EPU and insurance premiums can provide insights into broader economic trends and policy decisions. EPU is often driven by political and economic events, and understanding its impact on insurance premiums can provide valuable information about how policy decisions and other external factors can affect the insurance industry and the broader economy. To understand the impact of EPU, this research examines the nexus between EPU and insurance premiums across 22 countries from 1996 to 2020. By applying panel cointegration tests, and the PMG-ARDL regression, it is found a periodical (both short-term and long-term) influence of EPU on insurance premiums. Additionally, it is revealed that EPU has a longer-term consequence on insurance premiums than it does in the short run. Also, EPU has a greater role in life insurance than non-life insurance. The results are consistent when robustness techniques (FMOLS and DOLS) are applied. The findings of the article have major implications for the government, policymakers, insurance authorities, and other relevant stakeholders.